Relationship between the spirometric parameters and ECG parameters in children with bronchial asthma - K. D. Abramovskaya; E. V. Tush; M. V. Boldova; A. V. Prakhov; A. I. Khaletskaya; T. I. Eliseeva (Аллергология и Иммунология в Педиатрии, 2023)
.